An analysis of the different spike attack arm swings used in elite levels of men's volleyball - Plawinski, M. P. (Queen`s University, 2008)
As part of this work, two preliminary studies were conducted that identified three possible swings used at the elite level of volleyball and the resulting ball velocities created using these swings. Therefore, the purpose of this work was to explore the kinematic aspects of the different spike attack arm swings (straight ahead (SA), cross body (CB) and outside (OS)) where each different swing was broken down into its constituent parts. Methods Six elite-level varsity players participated in this study. A motion tracking system was used to collect motion data which was used to calculate the kinematics of the upper arm during each of the swing types. A number of minimums and maximums were then calculated including maximum hand speed. To compare means between swings one-way ANOVA`s were used. Results Few differences were found between the swing types. The only difference seen between the SA CB swings was a more pronounced wrist flexion during the CB swing. It is possible that this helped propel the ball across the body during the CB. The OS swings differed from the CB and SA swings in that the OS was less horizontally adducted and there was a more pronounced external rotation during CB than during OS. These differences are likely to be responsible for the ball being hit away from the midline of the body during the OS swing. Typically, the hand speed results agreed with those of the study done previously concerning resulting ball speeds when these swings were employed. Conclusions Between the SA, CB and OS swing types, only the OS was consistantly different throughout the three studies. It is recommended that future studies attempt to examine the whole body during these types of swings. Also, it appears that elite-level players may be quite different kinematically, and each one should be treated as a separate case in a training situation. The findings of these studies may help coaches, trainers and athletes develop better training, injury prevention and rehabilitation programs in the sport.